(untitled) (Research, Society and Development, 2023)
Introduction: Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder characterized by difficulties in social interaction, communication, and repetitive and restricted behaviors. Its prevalence has increased considerably in recent decades. Although a large proportion of people with ASD enter higher education, a considerable portion, approximately 60% of these students, fail to complete their degrees. Objective: to identify the main challenges faced by academics with ASD at university. Methodology: This is a qualitative exploratory-descriptive study. A focus group interview was conducted with 3 students enrolled in the medical course of a public university in the north of Minas Gerais. The data obtained through the interview were classified and categorized for content analysis according to Bardin’s method, allowing inductively establish conclusions after analysis and interpretations. Results: several demands were identified, such as the lack of reception of the academic center by the university secretariat, preparation of tests with simpler language, adaptations in seminars, lack of information about ASD by teachers at the beginning of each tutoring and it was also identified that there is a good reception by teachers and students. Conclusion: The university needs to adapt to the reality of the students with ASD. The teaching staff needs training to deal with these students, in order to avoid embarrassment. The rights of the students need to be clarified and the support centers should be exposed.